Aplikasi Manajemen Proyek Berbasis Framework CodeIgniter dan Bootstrap di PT. Pura Barutama - Ramos Somya (Politeknik Harapan Bersama, 2018)
Pura Bangunan Unit of PT. Pura Barutama has responsibilities to handle new building construction and renovation of old buildings. The procedure of requesting memo to do that tasks are still processed by requesting to Pura Bangunan Unit to create a new memo. In addition, the project management process is often inaccurate and not real time. It is inefficient and ineffective because requesting memo takes 1-2 days. Sometimes, the collected requesting memo files are missing, and monitoring results are not optimal. This research will design and implement the management project application using CodeIgniter and Bootstrap framework. The results showed that the application helps and accelerates all units of PT. Pura Barutama to request a memo faster. Moreover, the memo requesting files can be stored safely and project management process can be done gradually, so that the monitoring results are accurate and real time. CodeIgniter framework made the code more simple and save. The use of Bootstrap also made this application accessible in a variety of screen sizes including on screen tablets and smartphones by providing responsive displays.